Rancang Bangun Prototype Sistem Informasi Peringatan Dini Dan Pencegahan Banjir Luapan Air Sungai Bendungan Pamarayan Berbasis Internet Of Things - Hendra, Yul; Yunita, Irma; Fahri, Alvin (Jurnal Ilmiah Sains dan Teknologi, 2023)
This research will raise a system of how to plan an early warning system for floods in areas around rivers, or what is commonly called an Early Warning System (EWS) to prevent flooding around rivers. This early warning system is built with hardware that uses the ESP 32 microcontroller to control the level of water release from the dam and select the floodgates to be opened automatically. Ultrasonic sensors are used to detect water levels, IOT modules are used to provide quick information to officers. The object of this research was carried out at the Gerak Pamarayan Dam, a dam that controls the two largest rivers in Banten, namely Ciujung and Ciberang. Two rivers flow in two districts in the Banten area. The method used in this study is the Prototype method. And the expected result of this research is to create an early warning system for overflowing river water that measures the water level of the river automatically and automatically reports the water level that is at the threshold to the officers and what is equally important is that this system can also prevent flooding due to overflow by how to open the floodgates automatically when the river water level is beyond the normal height threshold.